Negotiating Islamic Inheritance and Legal Ethics in Interfaith Families: Evidence from North Sulawesi, Indonesia - Bilalu, Naskur; Imamuddin (Antmind Review: Journal of Sharia and Legal Ethics, 2025)
Inheritance distribution in interfaith families poses significant ethical and legal challenges within Islamic law, particularly in pluralistic societies. This study examines how interfaith families in North Sulawesi, Indonesia, negotiate Islamic inheritance norms amid religious diversity and social realities. Employing qualitative field research, data were collected through in-depth interviews with members of interfaith families across several districts and cities in North Sulawesi. The findings reveal two dominant patterns of inheritance practice: collective utilization of inherited property without formal division and equal distribution among heirs regardless of religious affiliation. Although these practices diverge from classical Islamic inheritance rules that prohibit mutual inheritance between Muslims and non-Muslims, they are ethically motivated by the pursuit of family harmony, social cohesion, and conflict prevention. This study argues that such practices represent a form of ethical negotiation within Islamic law, reflecting principles of legal ethics, maqāṣid al-sharī‘ah, and legal pluralism rather than legal deviation. By situating local inheritance practices within broader debates on Islamic legal ethics and tolerance, this article contributes to contemporary discussions on how Islamic law responds to interfaith family realities in multicultural societies.